Effect of Al on the microstructure and mechanical properties of Mg–6Zn–2Sn–0.5Mn alloy. Issue 12 (13th August 2019) - Wang, Cong; Cui, Jie; Luo, Tianjiao; Liu, Yunteng; Wang, Changzheng; Hao, Xuehui; Yang, Yuansheng
ABSTRACT: The microstructure and mechanical properties of Mg–6Zn–2Sn–0.5Mn– x Al ( x = 0, 1, 2, 3) alloy are investigated. The addition of Al leads to the refinement of grain size and the formation of Al6 Mn, Mg32 (Al, Zn)49 also forms when the amount of Al is higher than 2 wt-%. Because of the addition of Al, the precipitates in the alloy after ageing treatment are refined. The alloy containing 1 wt-% Al shows good mechanical properties in the as-cast state which is attributed to the refined grains and low volume fraction of large second phases, it also shows high strength after ageing treatment resulted mainly from the homogeneously distributed fine precipitates, the yield strength, ultimate tensile strength and elongation are 183, 310 MPa and 11%, respectively.